The experiential basis of concepts: integrating embodied and enactive accounts - Fuchs, Thomas (Frontiers in Psychology, 2026)
The paper argues for an embodied and enactive view of linguistic concepts as a solution to the “scaling up” problem, namely the transition from embodied experience to symbolic and abstract thought. Drawing on phenomenology, neurobiology, conceptual metaphor theory and enactivism, it aims to demonstrate the constitutive role of the body and intersubjectivity in concept formation. Concrete concepts (“chair”, “table”, etc.) emerge from sensorimotor interactions with the environment which are transformed into simulated actions, while abstract concepts—such as “space”, “time”, “truth”, and others—arise both through metaphorical extensions of bodily experience and participatory sense-making in social contexts. Neurobiological findings support this view, showing strong connections between language processing, sensorimotor and social brain systems, and tracing language evolution to exaptation or reuse of motor coordination areas. Phenomenological analysis then highlights how bodily or operative intentionality underlies grammatical structures, and how concepts retain their roots in action and interaction even when abstracted. As examples, the study explores container schemas as the embodied basis of categorization and analyzes the bodily origins of space, time, causality, and moral concepts. In sum, concepts are not free-floating symbols but remain anchored in corporeal and intersubjective experience, thus integrating embodiment, language, and culture. Human reason proves to be not disembodied, but fundamentally rooted in embodied interaction and intersubjective practice.